In silico designing of thermostabe β-Glucuronidase (GUS) - Noorbatcha, Ibrahim Ali; Khan, Ayesha Masrur; Mohd. Salleh, Hamzah (2010)
This research has used Molecular Dynamics (MD) techniquess as an in silico method of correlating the experimental studies done on GUS enzyme with computational study and has analyzed and identified the structural factors responsible for thermostability of this enzyme. GUS from E. coli is heat labile and inhibited by detergents and products, which hinder its usefulness as a reporter molecules in genetic engineering. Therefore a more thermostable GUS enzyme needs to be designed for industrial applications. Using homology modeling, structures of mesophilic and thermophilic GUS enzymes from E. coli and T. maritima have been constructed based on the crystal structure of human GUS enzyme. MD simulations of these mesophilic and thermophilic GUS enzymes at temperatures of 300 K and 353 K in vacuum and implicit solvent have provided information on thermolabile regions in the enzymatic structure to be targeted for thermal stability. The RMS deviation of backbone atoms and helical residues from their initial coordinates was analysed for the resulting simulation trajectories. A higher number of charged residues found in the thermostable GUS were found to be responsible for stability of the helices compared to mesophilic GUS. From analysis of salt bridges, the presence of higher number of Glu-Arg and Glu-Lys salt bridge pairs were found to be responsible for be responsible for thermostability of T.maritima GUS The thermolabile residues 150-155 in wild type E. coli GUS structures were identified, and have been suggested as mutation points for experimental studies to improve thermostability. These residues have not been identified before, and are suggested to be replaced with Ala, Arg, Glu, and Lys. The choice of Ala and Arg are supported by previous experimental mutations in other regions of GUS and have resulted in thermostable GUS enzymes.